Association between seed coat polyphenolics (tannins) and disease resistance in common bean - Islam, F.M.A.; Rengifo, J; Redden, R.J.; Basford, KE; Beebe, Stephen E. (Springer, 2003)
Common beans (Phaseolus vulgaris L) contain a number of antinutritional factors such as condensed tannins. Reducing tannin concentration might contribute to improving the nutritional quality of common bean. But polyphenolics are involved in resistance to diseases and pests, and reducing tannin concentration may have a negative effect on plant resistance. Furthermore, the effects of tannin on disease resistance in different gene pools or in different seed colors are not defined. To investigate these effects, 790 accessions from a common bean core collection were investigated. Data were subjected to independent sample t-tests, and the calculation of correlation coefficients. The mean coat extracts of black and red bean classes were highest (with 0.129 g/g and 0.124 g/g of seed coat, respectively). Among the gene pools, the coat extract was greater in the Middle American gene pool (0.129 g/g) than in the Andean gene pool (0.108 g/g). Coat extract in the Andean gene pool was positively correlated with susceptibility to Middle American isolates of anthracnose and to common bacterial blight, but negatively correlated with susceptibility to Andean isolates of angular leaf spot and to empoasca. Only empoasca damage showed negative correlation with coat extract in the Middle American gene pool. However within gene pools, the coat extracts of different seed classes varied in correlations with reactions to disease and pest infestations. Significant correlations were particularly associated with the black seed class in both gene pools. The relationships between coat extract and disease reactions are complex. A better understanding will help breeders to select germplasm with improved nutritional quality without adversely affecting disease resistance.